Synthesis and properties of novel lanthanide carboxyphosphonates - Pérez-Colodrero, Rosario Mercedes; Salcedo, Inés R.; Bazaga-García, Montse; Zon, Jerzy; Zareba, Jan K.; Olivera-Pastor, Pascual; Cabeza-Díaz, Aurelio (My University, 2021)
Metal phosphonates are essentially acidic solids featured by groups such as P-OH, -COOH, etc. The presence of bound and lattice water favors the formation of H-bond networks, which make these compounds appropriate as proton conductors, attractive for proton exchange membranes (PEMs) of Fuel Cells. Moreover, these properties can be enhanced by appropriate modification of the synthesis conditions. We report here, general characteristics of three new series of isostructural compounds resulting from the combination of the polyfunctional 5-(dihydroxyphosphoryl) isophthalate acid with lanthanide ions. All compounds were synthesized under hydrothermal conditions and their crystal structures were solved from powder X-ray diffraction data using synchrotron radiation. In contrast with Series III compounds, which exhibit a layered structure, Series I and II present pillared frameworks. All these compounds contain water molecules that contribute to the formation of H-bond networks. Upon exposure to ammonia vapour, from an aqueous solution, solid state transformations are observed which are accompanied of an enhancement of their proton conductivity properties.
Keywords: Química - Congresos; Conductividad - Congresos; Metal phosphonates; Coordination polymer; Proton-conductivity